Effect of different angulations and collar lengths of conical hybrid implant abutment on screw loosening after dynamic cyclic loading - Mai Ahmed Yousry El-Sheikh; Tamer Mohamed Nasr Mostafa; Mohamed Maamoun El-Sheikh (SpringerOpen, 2018)
Abstract Background The purpose of this in vitro study was to evaluate the effect of different angulations and collar lengths of the implant abutment on screw loosening by measuring removal torque value (RTV) before and after dynamic cyclic loading using digital torque gauge. Methods A total 90 sets of 4.5 mm diameter × 10 mm length bone level implants with conical hybrid connection were used. They were divided equally according to abutment angulation, into three groups: GI 0° abutment, GII 15° abutment, and GIII 25°. Each group was divided into two subgroups, 15 each, according to collar height: subgroup A (2 mm) and subgroup B (4 mm). Each implant and abutment assembly was positioned vertically in the center of the acrylic resin block using stainless steel cylindrical split mold. Initial analysis was made by abutment screw tightened with 30 Ncm torque twice with 10-min intervals using a digital torque gauge. RTV before and after cyclic loading of the abutment screws were measured in newton centimeter using digital torque gauge. One hundred thousand cycles of eccentric dynamic cyclic loading, at 130 N at a rate of 1 Hz, were applied 5 mm away from the central axis of the implant fixture. Percentage of removal torque loss (%RTL) before and after dynamic cyclic loading were calculated and statistically analyzed using the SPSS version 20. Results For GI, %initial RTL was 25.0 ± 1.5% and decreased significantly after loading (23.5 ± 2.3%). For GII, %initial RTL was 25.5 ± 1.4% and increased significantly after loading (33.4 ± 3.7%). For GIII, %initial RTL was 25.944 ± 1.2% and increased significantly after loading (40.1 ± 5.1%). There was significant effect on screw loosening for abutment angulations and collar lengths. Conclusion Within the limitations of this study, results suggested that screw loosening increases with increasing abutment angulations and collar lengths after dynamic cyclic loading.